Cartilage issues in football - today's problems and tomorrow's solutions - Mithoefer, K.; Peterson, L.; Zenobi-Wong, M.; Mandelbaum, B. R. (British Journal of Sports Medicine, 2015)
Articular cartilage injury is prevalent in football players and results from chronic joint stress or acute traumatic injuries. Articular cartilage injury can often result in progressive painful impairment of joint function and limit sports participation. Management of articular cartilage injury in athletes aims to return the player to competition, and requires effective and durable joint surface restoration that resembles normal hyaline articular cartilage that can withstand the high joint stresses of football. Existing articular cartilage repair techniques can return the athlete with articular cartilage injury to high-impact sports, but treatment does not produce normal articular cartilage, and this limits the success rate and durability of current cartilage repair in athletes. Novel scientific concepts and treatment techniques that apply modern tissue engineering technologies promise further advancement in the treatment of these challenging injuries in the high demand athletic population. We review the current knowledge of cartilage injury pathophysiology, epidemiology and aetiology, and outline existing management algorithms, developing treatment options and future strategies to manage articular cartilage injuries in football players.